Thermal Oxidative Decomposition of Soybean Straw: Thermo-Kinetic Analysis via Thermogravimetric Analysis and Artificial Neural Networks. Issue 1 (November 2020) - Xie, T; Wei, R C; Gong, C Z; Wang, J
Abstract: Keeping in view the energy shortage problem, the bioenergy potential of soybean straw have been evaluated by thermos-kinetic study using thermogravimetric analysis and artificial neural networks. TG-DTG curves at 10, 20, and 30°C min −1 revealed that the thermal oxidative decomposition of soybean straw could be divided into three stages and the second stage (180 to 380°C) would be the most suitable for thermal conversion of soybean straw into energy and chemicals. Kinetics analysis results showed that the activation energy values of models ranges were: KAS (87.57-819.24 KJ mol −1 ), and OFW (92.01-790.85 KJ mol −1 ), respectively. The variation of activation energy indicated the thermal decomposition process of soybean straw is complicated and may be consisting of several reactions. Furthermore, an ANN model was applied to predict the thermal decomposition of soybean straw. The good fitness between experimental and predict data ( R 2 = 0.999) validated the accuracy of the model in predicting the mass loss of thermal oxidative decomposition process.